Evaluation The Reality Of The Dimensions Of Solid Design In Iraqi Industrial Companies _ Crescent Industrial Company Model - Hadjidj, Mememar Abdelah Mohamed (Finance and Business Economies Review, 2019)
The study investigates the role of a modern concept in the field of production at the field and knowledge level, which is represented by the determination of the solid in the local industrial companies, by seeking to assess the actual reality of the design dimension by examining the opinions of a sample of the employees of Crescent Industrial Company (40) A questionnaire questionnaire prepared for this purpose and distributed to the sample was retrieved in full and a number of appropriate statistical tools were used to process and analyze the data. In the light of these results, a number of conclusions were reached, the most prominent being the interest and commitment of the Department of Evil Under the adoption of the dimensions of solid design, and according to the findings of these research was presented a number of proposals in this regard from the most important, the need to strengthen the company's efforts under management after the flexibility, as a complement to the dimensions of a solid design in the company in question.